2016
DOI: 10.18632/oncotarget.8959
|View full text |Cite
|
Sign up to set email alerts
|

Novel 1, 3-N, O-Spiroheterocyclic compounds inhibit heparanase activity and enhance nedaplatin-induced cytotoxicity in cervical cancer cells

Abstract: Heparanase (HPA) is an enzyme that plays an important role in cancer metastasis and angiogenesis and is a potential target for molecular treatment of tumors. We previously found that abnormally high HPA expression in cervical cancer tissues is associated with poor survival and increased lymph node metastasis. The present study was conducted to assess the utility of inhibiting HPA enzyme activity in cervical cancer treatment. Two series of 13 novel HPA inhibitors were synthesized and optimized. All tested inhib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 24 publications
1
8
0
Order By: Relevance
“…This result is consistent with one previous study, which used NDP on human gastric cancer AZ-521 cells [21]. Other studies also found that different cisplatin drugs have similar effects on cell cycle in different cancer types [22][23][24], suggesting that cell cycle blockage in S phase may be one of the mechanisms in which NDP-induced apoptosis [25]. In our study, we found that apoptotic rate increased significantly in NDP or MVIH siRNA treated MDR cells, indicating that NDP could improve chemotherapeutic sensitivity of A549 and H1650 cells and promote apoptosis by down-regulating MVIH.…”
Section: Discussionsupporting
confidence: 93%
“…This result is consistent with one previous study, which used NDP on human gastric cancer AZ-521 cells [21]. Other studies also found that different cisplatin drugs have similar effects on cell cycle in different cancer types [22][23][24], suggesting that cell cycle blockage in S phase may be one of the mechanisms in which NDP-induced apoptosis [25]. In our study, we found that apoptotic rate increased significantly in NDP or MVIH siRNA treated MDR cells, indicating that NDP could improve chemotherapeutic sensitivity of A549 and H1650 cells and promote apoptosis by down-regulating MVIH.…”
Section: Discussionsupporting
confidence: 93%
“…Despite the improvement of therapeutic methods and diagnostic tools, the overall prognosis of patients has not been improved . Many patients do not respond well to any currently available treatments . Therefore, exploration of pathogenesis and identification of novel biomarkers is imperative.…”
Section: Introductionmentioning
confidence: 99%
“…2,9 Many patients do not respond well to any currently available treatments. 10 Therefore, exploration of pathogenesis and identification of novel biomarkers is imperative.…”
mentioning
confidence: 99%
“…Importantly, 55 strongly reduced the mRNA and protein levels of heparanase. This study suggested that targeted inhibition of heparanase may prove to be an effective therapy against cervical cancer (Song et al., 2016).…”
Section: Synthetic Heparanase Inhibitorsmentioning
confidence: 94%